2019
DOI: 10.3389/fpubh.2019.00328
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Early Childhood Caries in Canadian Children and Associated Risk Factors

Abstract: Introduction: Early childhood caries (ECC) is any caries in the primary dentition occurring in children under the age of six. ECC is common in many population groups in Canada. Objective: The purpose of this review was to describe the burden of ECC in Canada, the prevalence and associated risk factors for ECC, and its impact on childhood health based on the existing published literature. Methods: A review was conducted to assess published Canadian studies on ECC identified through searches of electronic databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 51 publications
4
64
0
1
Order By: Relevance
“…Additionally, Levy et al had showed a statistically significant association between low intellectual capabilities and higher dental treatment needs among IDF soldiers, and implied for an association with parental education, similarly to other published studies and to the current study results [14,16,17]. Parental education level had been previously found to be associated with oral health outcomes, and specifically, with caries prevalence in many studies [18][19][20]. The odds of having any caries experience (DMFT > 0) were found to be significantly greater in those with low parental educational or occupational background [21], thus, the results of the current study support former evidence.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Additionally, Levy et al had showed a statistically significant association between low intellectual capabilities and higher dental treatment needs among IDF soldiers, and implied for an association with parental education, similarly to other published studies and to the current study results [14,16,17]. Parental education level had been previously found to be associated with oral health outcomes, and specifically, with caries prevalence in many studies [18][19][20]. The odds of having any caries experience (DMFT > 0) were found to be significantly greater in those with low parental educational or occupational background [21], thus, the results of the current study support former evidence.…”
Section: Discussionsupporting
confidence: 88%
“…Mean DMFT was 4.2-5.98 (with standard deviation of 3.9-4.8) for a wide range inhomogeneous age group of 18-29-year-old participants. In a very local survey, mean DMFT among [18][19] Israeli military recruits was 6.09 ± 5.29 with 17.2% caries free rate [3]. Since these publications, no representative national epidemiological survey regarding caries prevalence in Israel among 18 years old has been published yet, nor did any additional study of caries prevalence among this age group, although this age group is defined by the World Health Organization (WHO) as an index group.…”
Section: Introductionmentioning
confidence: 99%
“…There are several possible direct and indirect explanations for a relationship between preterm birth and early childhood caries. Preterm birth is strongly associated with enamel defects, 26,27 and such hypomineralizations are predisposing for caries development 28 . Preterm birth and immature immunity are also linked to an early oral colonisation of Streptococcus mutans and other acid‐tolerating strains with cariogenic properties 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Preterm birth is strongly associated with enamel defects, 26,27 and such hypomineralizations are predisposing for caries development. 28 Preterm birth and immature immunity are also linked to an early oral colonisation of Streptococcus mutans and other acid-tolerating strains with cariogenic properties. 29,30 Early-in-life treatment with antibiotics can affect the composition of the developing microbiota with a disturbed abundance of commensal genera.…”
Section: Ta B L E 1 Characteristics Of the Included Studies On Pretermentioning
confidence: 99%
“…Overall, within the present study the influencing factors were considered within a cohort of children with increased dental treatment demand who can be considered as a high-risk group. Socioeconomic factors at the community and family level, such as ethnicity are well-recognized determinants of oral health and identified as risk factors in several studies reviewed [ 32 34 ]. Parental education and employment status are also known to influence caries development [ 35 ].…”
Section: Discussionmentioning
confidence: 99%